Covid-19 Fatality Rate in Third World Countries: A Review of Environmental Challenges and Impacts on Public Health and Human Security - Etodike, Chukwuemeka E.; Ekeghalu, Elsie C.; Ani, Kelechi Johnmary; Mutambara, Emmanuel (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
The novel coronavirus is far from being over; with the case-fatality rate (CFR) hitting more than 16,500 globally as of July, there is a worry that despite the fact that the global CFR curve is showing signs of flattening, the environmental peculiarities of the third world countries may be abetting global efforts towards containing the virus. Therefore, this review x-rayed these peculiarities in the light of their current concern in public health as per their contribution to the persistent surge in CFR in most developing nations. Given that the virus is transmitted via droplets, the review focused on how the state of public and environmental challenges such as air as well as water pollution and personal hygiene could be abetting the surge in coronavirus infections and morbidity. The review revealed, among other things, that challenges associated with poor sanitary conditions, lack of potable water, unventilated environments, air pollution, and poor inter-personal hygiene are devastating challenges in the fight against the pandemic. The implication is that since these conditions are systematic in nature, it may take more than average effort and public sacrifice to checkmate the case-fatality rate of the virus in the third world. Therefore, call for studies is necessary to establish empiricism for CFR patterns and ratio across areas in deplorable environmental and sanitary conditions.